Hur miljöpåverkan av hormonella preventivmedel diskuteras under rådgivning - En enkätstudie om kvinnors självrapporterade upplevelser vid rådgivning kring preventivmedel/metoder - Bengtsson Gravander,Alice (2016)
Since findings of intersex roach in the 1990s it has been clear that hormonal contraceptives has an impact on the aquatic environment via leakage from the sewage treatment plants. This study aims to investigate how women in Sweden experience the counselling they receive on contraceptives in regards to their environmental effects. To investigate this a survey was performed and 795 women in all ages participated. The study found that the environment was brought up in 6 % of the counsel sessions, mostly by the women themselves (in 65 % of the cases). Most of the women who discussed the environment in counselling (53 %) had an education in either environmental science or biology and the majority (58 %) was currently studying on a higher level (university or college). There was no clear patterns in age, ethnicity, demography, income, relationship status or recent child birth amongst those who brought up the environment. The environment received the lowest amount of time in counselling, while the subject most discussed was the contraceptives function and their effect on the human body. The participants exhibited that midwifes and/or gynecologists tended to inform about the hormonal contraceptives in much larger extent than the hormonal free (with exception from the copper IUD). Further the study showed that the majority of the participants (91 %) wanted to receive information about the contraceptives effect on the environment to be able to make conscious and informed decisions. In order to address this environmental issue, information has to be available for all involved in the distribution and choice of contraceptives, along with improving the effectiveness of cleaning waste water in sewage treatment plants.
Keywords: hormonella preventivmedel; miljöeffekter; enkätstudie